Behavior of Stock Price Variability over Trading and Nontrading Periods, and Daily Return Volatility - Sumiyana, Sumiyana (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2007)
This study examined the behavior of stock price variability over trading and nontrading periods, and daily return volatility. This study used intraday data in Indonesia Stock Exchange. Sample was taken from the firms listed in LQ 45 indexes for the year of 1999-2006. The behavior of stock price variability and daily return volatility, according to previous theories, is influenced by the array of public and private information.This study concludes that return variance over trading and nontrading periods, along with overnight and lunch break nontrading session, and the first and second trading session, has differed significantly. In addition, daily return volatility is also not identical significantly. Subsequently, this study used size, trading volume, bid-ask spreads and up-down market as control variables. This study contradicts to all prior studies. This study especially suggests contra evidence in comparisons with previous concepts and theories in regards to size, trading volume, bid-ask spreads, and up-down market as control variables.